2015
DOI: 10.1016/j.chemosphere.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Performance and fate of organics in a pilot MBR–NF for treating antibiotic production wastewater with recycling NF concentrate

Abstract: h i g h l i g h t sMBR-NF with NF concentrate recycling was tested for antibiotic-wastewater treatment. The system was effective for antibiotic production wastewater treatment and reuse. The MBR-NF process resulted in excellent water quality and a high water yield of 92%. Organic pollutants in the wastewater were almost completely retained by the NF. a r t i c l e i n f o b s t r a c tA double membrane system comprising a membrane bioreactor (MBR) combined with a nanofiltration (NF) membrane was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 33 publications
(38 reference statements)
2
22
0
Order By: Relevance
“…However, VRF had little impact on NF permeate with TOC stable at approximately 2 mg/L. These results suggested that the steady performance of NF guarantees the removal efficiency of organic matters by the MBR-NF process with the backflow of NF concentrate, which is in good agreement with results reported in other literatures (Kappel et al 2014;Wang et al 2015;Wang et al 2014). The MW distribution of organic matters at VRF = 5 in the MBR-NF process is shown in Fig.…”
Section: Nf Permeate Flux and Water Recoverysupporting
confidence: 82%
See 1 more Smart Citation
“…However, VRF had little impact on NF permeate with TOC stable at approximately 2 mg/L. These results suggested that the steady performance of NF guarantees the removal efficiency of organic matters by the MBR-NF process with the backflow of NF concentrate, which is in good agreement with results reported in other literatures (Kappel et al 2014;Wang et al 2015;Wang et al 2014). The MW distribution of organic matters at VRF = 5 in the MBR-NF process is shown in Fig.…”
Section: Nf Permeate Flux and Water Recoverysupporting
confidence: 82%
“…Nevertheless, the effect of NF concentrate at diffident backflow ratios (R cb s) remains unclear while the suitable VRF for NF concentrate also needs some attention. In addition, few studies (Wang et al 2015;Wang et al 2014) were reported working on the advanced treatment and reclamation of the real antibiotic production wastewater by the MBR-NF process. Further research on the parameter optimization and mechanism study for the application of the MBR-NF process in antibiotic production wastewater treatment are imperatively needed.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The Figure S2a, the peak at 2500-3700 cm −1 is suggested to represent the stretching of the O−H bond [54] and 1413 cm −1 (C−N stretch) may indicate the secondary and tertiary amines. Figure S2b spectra exhibits absorption band around 1052 cm −1 , which can be assigned to the C−O stretching of polysaccharides or polysaccharide-like substances [55] and 1157 cm −1 band suggested to be assigned to C−O bond of ethers or carboxylic acid [53]. Figure S2b also showed three groups of bands near 1762, 1652, and 1578 cm −1 [56] in fouling layer after NaOH, NaOCl and citric acid cleaning.…”
Section: Ftir Analysismentioning
confidence: 89%
“…were detected in the range of 1350-1260 and 1075-1000 cm −1 , respectively, which were derived from the polysaccharide-like substances (Chon et al, 2012a(Chon et al, , 2012bWang et al, 2015). The O-H stretching and C-H stretching that occurred in the range of 3500-3300 and 3000-2800 cm −1 were related to proteins, humic acids and polysaccharides, and it was difficult to distinguish the derivation of these functional groups based on IR analysis.…”
Section: Ft-ir Analysismentioning
confidence: 99%